Activity diversity is associated with the prevention of frailty in community-dwelling older adults: The Otassha Study - Takahashi, Junta; Kawai, Hisashi; Ejiri, Manami; Fujiwara, Yoshinori; Hirano, Hirohiko; Sasai, Hiroyuki; Ihara, Kazushige; Ishii, Kaori; Oka, Koichiro; Obuchi, Shuichi (Frontiers in Public Health, 2023)
A prior study showed an association between diversity in daily activities (type, frequency, evenness) and frailty in older adults. However, the causality of this relationship is unclear. Therefore, this study aimed to clarify the relationship between activity diversity and frailty through a 2-year longitudinal study conducted among community-dwelling older adults. We evaluated data from the 2018 and 2020 waves of the Otassha Study. Frailty was assessed using the Cardiovascular Health Study criteria, with pre-frail and frail participants defined as frail and the other participants categorized into the robust group. We enrolled a total of 207 participants who were not frail at baseline. Activity type, frequency, and evenness scores were calculated using an Activity Diversity Questionnaire. The association between each activity diversity score and the incidence of frailty was evaluated using logistic regression modeling (each diversity score was entered the model after Z-transformation). Of the 207 enrolled participants (median age, 73 years; age range, 65–91 years; 60.4% women), 64 (30.9%) had incident frailty during the follow-up period. A logistic regression analysis adjusting for sociodemographic and psychosomatic factors revealed odds ratios for activity type and evenness scores of 0.64 and 0.61, respectively (P<0.05). These factors were significantly associated with the incidence of frailty. Activity type and evenness (except frequency) within daily activities were predictors of frailty during 2 years of follow-up. Engagement in diverse activities appears to be more effective in preventing frailty than does engagement in a few activities.